PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Abd. Rohman; Yayang Hanafi; Willy Tri Hardianto (Universitas Tribhuwana Tunggadewi, 2019)
The Government’s duty other than the Government conducting a public service that is characterized by good governance. In Lowokwaru, time service itself became one things to note again. This can hamper service rendered to the society. In addition to the time of service, service officer presence also the things that can hinder the effectiveness and efficiency of the public services which are given to the community. This study uses qualitative methods. Using data collection techniques interviews, observation, and documentation. Determination of sampling techniques using the purposive addition. Data was analyzed through data reduction stage, the presentation of data, and the withdrawal of the conclusion. Validity test of the data, researchers used triangulation techniques. Research results application of the principles of good governance in improving the quality of public services in Lowokwaru already going pretty well. But in some aspects still contained flaws. It a barrier among other less familiar society requirements, service officers not to enter the work, power outages, as well as the network is unstable. Things that support among other hospitality-giver services officer, completeness of facilities and infrastructure, as well as the competence of the officers the service givers.